2016
DOI: 10.18512/1980-6477/rbms.v15n2p305-317
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Agronômico de Genótipos de Milho Pipoca no Nordeste do Estado do Pará

Abstract: RESUMO-O cultivo do milho pipoca pode ser uma boa alternativa para pequenos produtores do Nordeste do Pará pela similaridade do cultivo em relação ao milho convencional e pelos preços alcançados pelo milho pipoca, superiores ao milho comum. O objetivo do trabalho foi avaliar diferentes genótipos de milho pipoca quanto a caracteres agronômicos e capacidade de expansão (CE) dos grãos sob condições do Nordeste paraense. Foram realizados dois ensaios em blocos ao acaso para a avaliação de 29 híbridos e 25 populaçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Popping expansion may be affected by several factors. Several studies have reported the effects of genotype (PHUMELELE et al, 2014), starch composition and structure (BORRAS et al, 2006), physical properties (PORDESIMO et al, 1990), yield components (LI et al, 2008), chemical composition (PARAGINSKI et al, 2017), agronomic characteristics (SOUSA et al, 2016) and kernel water content. However, none of those studies investigated the potential relationship between micromorphology and popping expansion in popcorn.…”
Section: Introductionmentioning
confidence: 99%
“…Popping expansion may be affected by several factors. Several studies have reported the effects of genotype (PHUMELELE et al, 2014), starch composition and structure (BORRAS et al, 2006), physical properties (PORDESIMO et al, 1990), yield components (LI et al, 2008), chemical composition (PARAGINSKI et al, 2017), agronomic characteristics (SOUSA et al, 2016) and kernel water content. However, none of those studies investigated the potential relationship between micromorphology and popping expansion in popcorn.…”
Section: Introductionmentioning
confidence: 99%